The effect of overhand vs. underhand arm swing approach in a pre-flight vault - Donati, A.; Kabnick, H.; McDonald, A.
In determining the effect of arm swing approach in a preflight drill for a handspring vault, important performance indicators must be considered. In attempting to achieve the optimum handspring vault, there are three important factors that strongly affect performance: hip angle on the horse, shoulder angle on the horse, and ankle joint velocity (used to indicate speed with which the subject reaches the handstand position on the horse). In our analysis, we found that there were significant differences in these performance variables when comparing the underhand and overhand approach techniques. Hip angle in the underhand position achieved much greater hyperextension than that in the overhand position. In addition, the hip angle extended from the onset of the heel drive phase in the underhand approach and continued throughout the movement while there was a slight period of flexion observed in the heel drive phase of the overhand approach. In examining shoulder angle, the underhand approach did not display full shoulder extension on the horse (540 degrees - max/527 degrees - achieved) while the overhand approach was only slightly shy of full extension (180 degrees - max/178 degrees - achieved). Lastly, when looking at velocity of the ankle joint, the underhand approach dominated in both vertical and horizontal components and therefore, the underhand approach had a greater resultant velocity. Hip angle is an important factor because in order to perform a handspring that will quickly turn over into a handstand position on the horse, the hips must be extending throughout the heel drive phase. With hip extension, the lower limbs will serve to drive the center of gravity upward and will propel the subject forward once she is inverted on the horse. When the hips flex in the initial moments of the heel drive phase, the body turns over at a slower rate because the lower limbs trail the center of mass and fail to drive it over top of the horse. This was observed in the study with the overhand approach. With the overhand approach having a slight period of flexion on the horse during the heel drive phase, there was a very significant decrease in horizontal, vertical, and resultant velocities in the late phases of the movement. This is an undesirable condition, as the preflight is a drill for the handspring that will require rapid propulsion from the horse; the slower velocity of the overhand approach will hinder the speed of propulsion. Shoulder angle on the horse was also slightly different in each of the approach techniques. The underhand approach results for shoulder angle indicated failure to reach full extension while the overhand approach results indicated that full extension was achieved on the horse. In terms of future skills, as previously stated, the goal of the athlete will be to achieve a quick propulsion off of the horse. Having a slight shoulder angle in the preflight drill provides room for further extension that will allow for an extra boost off of the horse referred to as "blocking" when performing a handspring. The shoulder angle that is fully extended on the horse will lack the extra boost that comes from further extension. With regard to ankle joint velocity, all components of velocity were greater in the underhand approach. This would again contribute to a more successful propulsion off of the horse when performing a handspring. In looking at the results of our study as well as the performance factors that are necessary to make the preflight a useful drill for the optimum handspring, it appears that use of the underhand arm swing approach will be a more successful technique for future skill development. While we were content with the outcome of our study, we also understand that there are some potential limitations involved with such a study that should be noted. One limitation was the fact that only one subject was used for our study. Our study didn't account for other athletes that might be successful in using the overhand approach technique (whether it be due to excessive strength, abilities or other factors). More subjects would also be likely to give the data more validity. Another limitation involved with our study was the lack of high precision in digitizing joint markers on our subject. While we feel this would only account for slight errors or noise, it is still notable.